Differential responses of soil C, N, and P ecological stoichiometric characteristics to different configurations of edge-locked forests in the Kubuqi Desert - Chen, Xue; Zuo, Hejun; Yan, Min; Wang, Haibing; Xi, Cheng; Chai, Yinchao (Frontiers in Plant Science, 2025)
As a vital component of the desert ecological protection system, the edge-locked forests of the Kubuqi Desert play a crucial role in mitigating wind erosion, stabilizing sand, maintaining soil and water, and restricting desert expansion. In this paper, six types of standard protection forests in the Kubuqi Desert, namely Salix psammophila (SL), Elaeagnus angustifolia (SZ), Salix matsudana (HL), Corethrodendron fruticosum+Salix psammophila (YC + SL), Caragana korshinskii + Populus simonii (XYY + NT), and Elaeagnus angustifolia + Salix matsudana (SZ + HL), were investigated. Notably, the vertical differentiation patterns of soil carbon (C), nitrogen (N), phosphorus (P), and ecological stoichiometric ratios, as well as soil particle size features within the 0–100-cm soil layer under protection forests with different allocation modes, were systematically and comprehensively analyzed. The study’s findings showed that: (1) Among the six configuration types, SZ, NT + XYY, and SL exhibited higher soil SOC and TN concentrations. Both soil SOC and TN content decreased with increasing soil depth, whereas soil TP content displayed no considerable variation among different stand types or soil depths. (2) Based on the N/P threshold hypothesis, N was the limiting nutrient element for the growth of edge-locked forests in the region. (3) The understory soils of different configurations of edge-locked forests mainly comprised sand. The silt and clay contents of SL and NT + XYY were substantially higher than those of the other four configurations. The vertical distribution patterns of particle size and parameter characteristics had variations. (4) Soil C, N, P, and stoichiometric characteristics are affected by vegetation type, soil depth, and soil texture. In conclusion, SZ and SL can be used as the dominant tree species in the edge-locked forests of the Kubuqi Desert, and the NT + XYY mixed forest configuration pattern displays the most apparent soil improvement effect. This study’s findings offer a scientific reference and foundation for restoring vegetation and enhancing the ecological environment in desert regions. In addition, they provide a theoretical foundation for establishing and managing edge-locked forests.